THE ROLE OF HUMAN RESOURCE MANAGEMENT IN THE DIGITAL ERA IN IMPROVING THE QUALITY OF PRIMARY SCHOOL EDUCATION - Sulistyowati, Dheni; Rinda, Ida (PT. Antis International Publisher, 2025)
Objective: To analyze the role of human resource management (HRM) in the digital era in improving education quality in elementary schools, focusing on challenges, barriers, and relevant strategies for effective HRM in digital educational environments. Method: This study employed a Systematic Literature Review (SLR) approach to identify, evaluate, and synthesize findings from previous research. Qualitative and quantitative data analysis was conducted to explore the relationship between HRM practices and education quality in the context of the digital era. Results: The study highlights the crucial role of HRM in developing educators' digital skills, optimizing technology for performance management, and ensuring a supportive work environment for mental and physical well-being. Key challenges include resistance to change, limited infrastructure, and the digital divide. Innovative HRM strategies, such as continuous training, technology-enabled recruitment, and data-driven performance management, are identified as effective solutions to enhance education quality in elementary schools. Novelty: This study provides practical recommendations for implementing innovative HRM strategies to address the challenges of the digital era. It bridges the gap between HRM practices and their direct impact on education quality, offering insights into adapting HRM for global and technological advancements.